2013
DOI: 10.1038/nsmb.2629
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of a helicase loading intermediate containing ORC–Cdc6–Cdt1–MCM2-7 bound to DNA

Abstract: In eukaryotes, the Cdt1-bound replicative helicase core MCM2-7 is loaded onto DNA by the ORC-Cdc6 ATPase to form a pre-Replicative Complex (pre-RC) with a MCM2-7 double-hexamer encircling DNA. Using purified components in the presence of ATPγS, we have captured in vitro an intermediate in pre-RC assembly that contains a complex between the hetero-heptameric ORC-Cdc6 and the hetero-heptameric Cdt1-MCM2-7, called the OCCM complex. Cryo-EM studies of the 14-protein complex reveal that the two separate heptameric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
193
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 129 publications
(209 citation statements)
references
References 61 publications
14
193
2
Order By: Relevance
“…The Mcm3 CTE was shown to activate the ATPase activities of ORC-Cdc6 (Frigola et al 2013). The Mcm3 CTE partially protrudes from the end of the MCM hexamer, providing a structural basis for its function in the initial binding to ORC-Cdc6 (Frigola et al 2013;Sun et al 2013). Furthermore, its prominent position suggested that it could alter Mcm2-7 subunit interactions or influence Mcm2-7 ATP hydrolysis.…”
Section: Segmentation and Subunit Assignment Of The 3d Em Map Of Thesupporting
confidence: 89%
See 4 more Smart Citations
“…The Mcm3 CTE was shown to activate the ATPase activities of ORC-Cdc6 (Frigola et al 2013). The Mcm3 CTE partially protrudes from the end of the MCM hexamer, providing a structural basis for its function in the initial binding to ORC-Cdc6 (Frigola et al 2013;Sun et al 2013). Furthermore, its prominent position suggested that it could alter Mcm2-7 subunit interactions or influence Mcm2-7 ATP hydrolysis.…”
Section: Segmentation and Subunit Assignment Of The 3d Em Map Of Thesupporting
confidence: 89%
“…3D, 4). This is in stark contrast to the relative arrangement in the single Mcm2-7 hexamer and the Cdc45-Mcm2-7-GINS (CMG) helicase, where the NTD and CTD rings are vertically aligned (see the Discussion; Sun et al 2013;Costa et al 2014). …”
Section: Mapping the Architecture Of The Mcm2-7 Double Hexamermentioning
confidence: 87%
See 3 more Smart Citations